Spine morphogenesis and synapse formation in tubular sclerosis complex models - Shimada, Tadayuki; Yamagata, Kanato (Frontiers in Molecular Neuroscience, 2022)
Tuberous sclerosis complex (TSC) is caused by mutations in the Tsc1 or Tsc2 genes, whose products form a complex and inactivate the small G-protein Rheb1. The activation of Rheb1 may cause refractory epilepsy, intellectual disability, and autism, which are the major neuropsychiatric manifestations of TSC. Abnormalities in dendritic spines and altered synaptic structure are hallmarks of epilepsy, intellectual disability, and autism. In addition, spine dysmorphology and aberrant synapse formation are observed in TSC animal models. Therefore, it is important to investigate the molecular mechanism underlying the regulation of spine morphology and synapse formation in neurons to identify therapeutic targets for TSC. In this review, we focus on the representative proteins regulated by Rheb1 activity, mTORC1 and syntenin, which are pivotal downstream factors of Rheb1 in the alteration of spine formation and synapse function in TSC neurons.